ADAPTASI KURIKULUM MERDEKA DENGAN MODEL PEMBELAJARAN BERBASIS PROBLEM SOLVING PADA PENDIDIKAN AGAMA KRISTEN - Tri Setyo Heriyati (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
The Merdeka Curriculum was developed using a more flexible methods and focuses on essential material by developing the character and competence of students. Emphasizes project-based learning and soft skills development so that it is closer to practice in the world of work. On this basis, in some subjects it is necessary to adjust the learning model used to support these Curriculum. By using a literature review approach, the problem-solving-based learning models in Christianity education is an effort to adapt the Merdeka Curriculum, which was previously more often delivered by conventional methods. The presentation of the study explains that problem-solving-based learning that prioritizes problem solving in learning activities can strengthen the reasoning power used by students and can provide a basic understanding of the material presented, especially in understanding the Bible as teaching material in Christian religious education. This learning method will bring students to actively search for verses and words in the Bible that are connected to the problems they face. The learning objectives with the problem-solving method will be easier for students to be able to understand the contents of the Bible through solving problems related to real practice.